Penerapan teknologi tepat guna pada proses produksi U-Neulheu Kelompok Masyarakat Aceh Besar [Implementation of appropriate technology in U-Neulheu Production by Community Group of Aceh Besar] - Safriani, Novi; Moulana, Ryan; Iskandar, Elvira; Haryani, Sri; Aisyah, Yuliani (Universitas Syiah Kuala, 2024)
U-Neulheu, a traditional Acehnese cooking spice made from roasted grated coconut, is typically produced using simple and limited equipment, leading to an inefficient production process. As a result, both the quality and quantity of the final product are often suboptimal. The integration of technology into the production process remains far from ideal. The aim of this community service activity aims to enhance the quantity and quality of U-Neulheu produced by local partners through the implementation of Appropriate Technology, such as a roasted coconut grinder and dryer. These improvements are expected to increase the partner's income level and living standards. The partners involved in this activity are a group of housewives who produce U-Neulheu in Cot Preh Village, Kuta Baro Sub-District, Aceh Besar District. The methods of this community service activity include counseling, the implementation of technology in the form of a roasted coconut grinder and dryer, as well as technical guidance. The results of the activity show that the partners greatly benefited from the application of this Appropriate Technology. The use of the roasted coconut grinder and dryer in the U-Neulheu production process made it more effective and efficient in terms of both time and cost. In addition, the quantity and quality of U-Neulheu products have also increased. The quantity increase is measurable by the higher number of products produced (50%), while the quality improvement is evident in the smoother and more hygienic products.